Histological Transformation and Clonal Relationship of Subcutaneous Marginal Zone B-Cell Lymphoma and Diffuse Large B-Cell Lymphoma. (22nd June 2022) - Abbott, James; Corean, Jessica; Laggis, Caroline; Halwani, Ahmad; Toydemir, Reha; Miles, Rodney; Florell, Scott; Wada, David
Abstract: Histological transformation (HT) is an exceptionally uncommon and poorly understood event where a low-grade or indolent B-cell lymphoma transforms into a more aggressive entity, typically diffuse large B-cell lymphoma (DLBCL). The pathogenesis is unclear; however, HT is associated with a worse prognosis. This article reports a unique case of marginal zone lymphoma (MZL) limited to skin/subcutis (confirmed with PET-CT) that subsequently developed DLBCL, followed by nodal MZL. We explored phenotypic, molecular genetic, and cytogenetic findings in subcutaneous MZL with HT to DLBCL and subsequent progression to systemic MZL. Shared clonal peaks between the tumors were demonstrated through immunoglobulin heavy chain PCR, and genomic microarray analysis revealed both unique genomic abnormalities and shared regions of copy-neutral loss of heterozygosity in all specimens. BCL-2 expression was present in the original subcutaneous MZL, lost on conversion to Primary cutaneous diffuse large B cell lymphoma (PCDLBCL)-NOS, and regained during subsequent transformation to systemic MZL. The PCDLBCL-NOS did not demonstrate FISH rearrangements for MYC, BCL2, and BCL6. Here, we describe the histologic, immunophenotypic, and cytogenetic abnormalities of the clonally related transformation of subcutaneous MZL, PCDLBCL-NOS, and eventual systemic MZL. The predominantly subcutaneous presentation of MZL may be associated with a more aggressive outcome and raises consideration for careful evaluation of patients who present with this pattern.